1985
DOI: 10.1136/pgmj.61.711.35
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid poisoning with suicidal intent: a report of 53 cases

Abstract: Summary A report of 53 cases of formic acid ingestion with suicidal intention is presented. The patients were seen in one hospital in Kerala State over a 3 year period. Fifteen patients died and 38 patients survived. The pattern of clinical features seen is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 2 publications
(2 reference statements)
1
40
0
Order By: Relevance
“…Histology analysis (Table 1) determined a complete lack of the respiratory epithelium of the trachea, edema of mucosa and submucosa of the trachea, thrombi and hemolysis inside the small vessels of the trachea, pulmonary edema, hemolysis and thrombosis in the lung vessels. These findings are connected with formic acid injury to the tissue and the effect on the coagulation system [6,19,20]. On the other hand, there were no significant injuries to the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 90%
“…Histology analysis (Table 1) determined a complete lack of the respiratory epithelium of the trachea, edema of mucosa and submucosa of the trachea, thrombi and hemolysis inside the small vessels of the trachea, pulmonary edema, hemolysis and thrombosis in the lung vessels. These findings are connected with formic acid injury to the tissue and the effect on the coagulation system [6,19,20]. On the other hand, there were no significant injuries to the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 90%
“…Due to the volatile nature of the acid, respiratory complications, such as toxic pneumonitis have been reported in patients who presented with formic acid ingestion 15,16 . Mathew and Dalus studied 302 patients admitted with formic acid ingestion and found that 44% had respiratory distress, 70.2% had metabolic acidosis, 47.4% had aspiration pneumonia, 33.8% had ARDS and 25.5% had chemical pneumonitis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…1 The latex is a sticky, milky colloid drawn off by making incisions into the bark and collecting the fluid in vessels in a process called 'tapping'. 1 It is then refined into rubber ready for commercial processing.…”
Section: Introductionmentioning
confidence: 99%
“…1 The latex is a sticky, milky colloid drawn off by making incisions into the bark and collecting the fluid in vessels in a process called 'tapping'. 1 It is then refined into rubber ready for commercial processing. 1 Latex is generally processed into either latex concentrate for manufacture of dipped goods or it can be coagulated under controlled, clean conditions using formic acid (rubber acid, FA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation